Duration of Vowels in Oriya: A Developmental Perspective - Prusty, Venkat Raman; Venkatesh, Lakshmi (Journal of All India Institute of Speech and Hearing, 2020)
The study investigated developmental changes in duration of vowels as produced by native Oriya speaking children. Effects of age, gender, vowel type and voicing of post vocalic consonants and their interactions on the duration of vowels in Oriya were examined. The six vowels in Oriya - //, /a/, /i/, /u/, /e/ and /o/ - were targeted for analysis. Duration of target vowel segment V1 embedded in V1CV2 productions of native Oriya speaking children (40 boys and 40 girls) ranging in age from 3-14 years and young adults (10 men and 10 women) were measured using PRAAT software. Results indicated that duration of vowels of this language decreased with increase in age. Intrinsic duration of vowels was dependent upon the type of vowel. Post vocalic voicing lengthened vowel duration as early as three years of age. No significant gender difference was observed. Developmental changes in vowel duration suggested differential control over vowel production. The age at which children’s productions reached adult like durations differed by vowel type and the context of vowel production. It was evident that early acquisition of vowel specifications involved an interaction between language specific features and articulatory predispositions associated with phonetic context.